Specific features of the South-Western suburbs of Leningrad during the siege, 1941– 1944 - Aleksiejev, Denis; Kozhemyakin, Aleksey; Minutina-Lobanova, Yuliya (City and War, 2021)
During the siege of Leningrad its South-Western suburbs, which now consist of Kirovskiy and Krasnoselskiy districts, had the most unusual fates. Krasnoselskiy district was the only part of modern St. Petersburg which was seized by Germans. Its inhabitants suffered from forced displacements and terror politics of the occupants. Kirovskiy, on the other hand, formed first line of the Soviet defense, besides its factories tried to keep on working. But, nevertheless, the both districts shared common features: hunger, artillery bombardment (from different sides), total destruction of infrastructure, depopulation. After the war the both districts turned into a large construction site, where first projects of Soviet-style large-panel construction were implemented. Now the districts possess a great number of places of memory connected to the World War II – old pillboxes, soldier cemeteries, monuments, memorial plates. Most of streets here are named to remind us events of the siege of Leningrad and the World War II.